Open-source modeling chain for the dynamic assessment of road traffic noise exposure. (May 2021) - Le Bescond, Valentin; Can, Arnaud; Aumond, Pierre; Gastineau, Pascal
Highlights: We present a multi-agent traffic noise modelling framework based on open-source tools. Noise emissions and propagation are calculated using the CNOSSOS European standard. Using MATSim, various multi-agent noise exposure scenari can be assessed. Abstract: In light of the growing concern about the adverse effects of noise pollution on health, a better understanding is needed of the relationships between urban transport and individual exposure. To improve the scientific community's modeling capabilities specific to this issue, we propose a noise exposure modeling framework that uses agent-based activity, multi-agent travel simulation and a European standardized noise emission and propagation model. Based on two open source software packages, MATSim and NoiseModelling, this framework aims to simulate the spatiotemporal distributions of daily individual activity and road traffic noise. The proposed approach allows to use the tools and methods proposed in the NoiseModelling software by importing MATSim outputs, therefore, taking full advantage of the development work carried out within the two communities. As such, it enables both characterizing the individual exposure to road traffic-related noise and investigating noise exposure inequality problems based on the attributes of individuals and their activities.